1999
DOI: 10.1084/jem.190.8.1049
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A1 Protease, an Exoenzyme of Pathogenic Neisseriae, Is a Potent Inducer of Proinflammatory Cytokines

Abstract: A characteristic of human pathogenic Neisseriae is the production and secretion of an immunoglobulin (Ig)A1-specific serine protease (IgA1 protease) that cleaves preferentially human IgA1 and other target proteins. Here we show a novel function for native IgA1 protease, i.e., the induction of proinflammatory cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IL-8 from peripheral blood mononuclear cells. The capacity of IgA1 protease to elicit such cytokine responses in monocytes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 61 publications
2
49
0
Order By: Relevance
“…The authors suggested that the pathophysiological events induced by these elevated levels of TNF-␣ might be required for meningococcal pathogenicity. We have recently shown that neisserial immunoglobulin A1 protease is a potent inducer of TNF-␣ in peripheral blood mononuclear cells (25). Likewise, meningococcal lipopolysaccharide is known to stimulate proinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the pathophysiological events induced by these elevated levels of TNF-␣ might be required for meningococcal pathogenicity. We have recently shown that neisserial immunoglobulin A1 protease is a potent inducer of TNF-␣ in peripheral blood mononuclear cells (25). Likewise, meningococcal lipopolysaccharide is known to stimulate proinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Lorenzen et al (302) studied the immunogenic and immunomodulatory properties of the neisserial IgA1 protease. They found that IgA1 protease acts like a modulin by stimulating the release of tumor necrosis factor alpha (TNF-␣), interleukin-1␤ (IL-1␤), IL-6, and IL-8 from peripheral blood mononuclear cells but not the regulatory cytokine IL-10.…”
Section: Iga1 Proteasesmentioning
confidence: 99%
“…In doing so did the structural (epitopes) alterations bring about in the protease domain the array of substrate specificities, or was it the other way around, i.e., as the different protease substrate specificities developed (possible impelling force/pressure mentioned above) through structural changes antigenic profiles also changed in the other two domains? This enigma appears apparent in the immunoglobulin A1 (IgA1) endopeptidases produced by a variety of human pathogens such as Neisseria gonorrhoeae, N. meningitidis, and Haemophilus influenzae (Lomholt et al, 1992;Lorenzen et al, 1999). They cleave with high specificity a single peptide bond in the hinge region of human IgA1 but not IgA2.…”
mentioning
confidence: 99%